2010
DOI: 10.1016/s1726-4901(10)70065-4
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Resonance Angiography and Doppler Scanning for Detecting Atherosclerotic Renal Artery Stenosis

Abstract: RDS might still be the diagnostic procedure of choice for screening outpatients for ARAS because it is inexpensive, convenient, able to detect severity, and avoids the use of contrast media. When RDS is negative in aged people who have smoked longer than 20 years, with coronary artery disease or serum creatinine > 4 mg/dL, MRA is recommended for further evaluation of ARAS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 43 publications
0
11
0
Order By: Relevance
“…Diagnosis was confirmed through renal artery Doppler scan performed by skilled technician. The scan result was considered positive if there was turbulence before and after stenosis, maximum flow velocity > 180 cm/sec at stenosis, end-diastolic velocity > 50cm/sec, post-stenotic drop in velocity, acceleration time > 0.07 seconds and slope of systolic upstroke < 3 m/s 2 or resistance index associated with stenosis or occlusion of the segmental arteries < 0.5 (Ng et al, 2010[ 26 ]). Though, existence or absence of ischemic tissue damage was sole decision of associated nephrology consultant based on clinical picture and Doppler result.…”
Section: Methodsmentioning
confidence: 99%
“…Diagnosis was confirmed through renal artery Doppler scan performed by skilled technician. The scan result was considered positive if there was turbulence before and after stenosis, maximum flow velocity > 180 cm/sec at stenosis, end-diastolic velocity > 50cm/sec, post-stenotic drop in velocity, acceleration time > 0.07 seconds and slope of systolic upstroke < 3 m/s 2 or resistance index associated with stenosis or occlusion of the segmental arteries < 0.5 (Ng et al, 2010[ 26 ]). Though, existence or absence of ischemic tissue damage was sole decision of associated nephrology consultant based on clinical picture and Doppler result.…”
Section: Methodsmentioning
confidence: 99%
“…Twelve of 25 studies reported accuracy as a main outcome. 12,14,[24][25][26][27][28][29][30][31]32,33 Six of those 12 studies reported high agreement with CVA, 14,30,33 SRA, 25,29 and MRA 24 (range: 81-98%). The remaining 6 of 12 studies reported either moderate, 28 low, 31 or a combination of the degree of agreement depending on the DUS parameter.…”
Section: Dus Versus Other Angiography Techniquesmentioning
confidence: 98%
“…12,14,[24][25][26][27][28][29][30][31]32,33 Six of those 12 studies reported high agreement with CVA, 14,30,33 SRA, 25,29 and MRA 24 (range: 81-98%). The remaining 6 of 12 studies reported either moderate, 28 low, 31 or a combination of the degree of agreement depending on the DUS parameter. 12,27,32 These studies were generally conducted using similar criterion measures (eg, MRA, SRA, and CVA).…”
Section: Dus Versus Other Angiography Techniquesmentioning
confidence: 98%
See 1 more Smart Citation
“…the time between the onset of the cardiac wave and the systolic peak [ 6 ]—an important predictor of stenosis. This parameter can be conveniently estimated during the Doppler ultrasound (DUS) examination, which is however inferior to PCA in regard to its ability of reconstructing anatomical details of the arterial system [ 7 ]. The intravascular ultrasound can be employed to estimate the level of stenosis or guide the stent placement, but its clinical use is reported mainly in relation to coronary and carotid arteries [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%